Recycled parenting or grandparents raising second generation offspring - Plisková, Barbora (e-Pedagogium, 2022)
This study addresses the subject of foster grandparenting of preschoolers. When foster caregivers take responsibility for childcare, they must be prepared to face many challenges in parenthood and to accept new roles that might be very stressful and demanding but also very satisfactory. The research aimed to discover and understand the perception of "parenthood" by foster parents and to discover main specifics of foster grandparents. Qualitative research methods were used; the data source was an interview with foster parents from pre-defined families based on specified criteria. The second method was an interview with a focus group with four professionals who deal with supporting these types of families. In conclusion, foster parenting is very demanding since foster grandparents can experience ambivalent and negative feelings in fulfilling new roles. On the other hand, own grandparents´ aging changes and diseases can make the second round parenting more challenging and temporary. These factors together with socio-cultural context, health functioning, and other factors, affect parental activities in specific social interactions.
Keywords: foster parenting; foster grandparents; parenting; parenthood.